Exploring the effects of real-time online cardiac telerehabilitation using wearable devices compared to gym-based cardiac exercise in people with a recent myocardial infarction: a randomised controlled trial - Mitropoulos, A.; Anifanti, M.; Koukouvou, G.; Ntovoli, A.; Alexandris, K.; Kouidi, E. (Frontiers in Cardiovascular Medicine, 2024)
Exercise-based cardiac rehabilitation (CR) is a non-pharmacological multidisciplinary programprogramme for individuals after myocardial infarction (MI) that offers multiple health benefits. One of the greatest barriers to CR participation is the travelling distance to the rehabilitation centre. Remotely monitored CR appears to be at least as effective in improving cardiovascular risk factors and exercise capacity as traditional centre-based CR. Nevertheless, the efficacy of a remotely monitored CR in people with recent MI has yet to be examined.Thirty people (8 women, 22 men) with CAD following a recent (i.e., < 4 week) MI were randomly allocated into two groups (online home-based and gym-based groups). The groups underwent a 26-week CR thrice per week. All patients performed the baseline and 24 weeks follow up measurements where peak oxygen uptake (𝑉 ̇O2peak), mean daily steps, distance and calories were assessed.The online group showed improved in mean daily steps (P<0.05) and mean daily distance (P<0.05) at 24 weeks compared to the gym-based group. The paired sample t-test showed that all the assessed variables were statistically (P<0.001) improved for both groups at 24 weeks.Pearson's r demonstrated positive correlations between 𝑉 ̇O2peak and mean daily distance (r= .375), and negative correlations between 𝑉 ̇O2peak and muscle (r= -.523) and fat masses (r= -.460). There was no exercise-induced adverse events during the study.Our findings might indicate that a real-time online supervised CR exercise programme using wearable technology to monitor the hemodynamic responses in CAD post MI patients is equally effective to a gym-based exercise programme.